Developing intercultural, interdisciplinary, and international teaching strategies to promote sustainability and human development (Jóvenes en la Ciencia, 2025)
As part of the Summer Research Program 2025 at the University of Guanajuato, three French students from the University of Caen Normandy participated in a project on inclusive education. Their project, titled "Developing intercultural, interdisciplinary, and international teaching strategies to promote sustainability and human development," aligns with UNESCO's fourth sustainable development goal. Despite their varied academic backgrounds, they shared a common foundation in social sciences, which aided their understanding of inclusive education.The program included enriching sessions on inclusive education, led by experienced professors, and hands-on activities emphasizing environmental awareness. During the Curso de Verano week, the students taught children aged 8 and 9 at Resplandor International, focusing on sustainable development and French culture through interactive and inclusive methods.This experience reinforced the students' belief in the importance of inclusive education, which values each child's unique contributions and adapts to their needs, creating a more equitable and effective learning environment.